Consumer-behavioural intention towards the consumption of functional food in Malaysia: their profiles and behaviours - Salleh, Hayatul Safrah (The Clute Institute for Academic Research, 2015)
Unhealthy eating behaviour has been linked to the risks of many chronic diseases all around theworld.Functional foods and its association with health benefits and reducing the risk of diseases open a promising avenue for consumers to pursue a healthier life as well as extending their life expectancy.This provides a great market opportunity for functional foods to be developed. Consequently, it has generated considerable consumer interest in functional food consumption. This study describes the profiles and behaviours of the consumers who are willing to consume functional foods in Malaysia. By using mall intercept surveys, data were collected from consumers shopping at hypermarkets in Malaysia. From the analysis undertaken, it was found that the level of consumer-behavioural intention to consume functional food is encouraging. The results indicated that behavioural intention towards functional food tends to be different across gender, age and marital status.However this study found that the extent of consumer-behavioural intention does not vary by ethnicity, religion, income and education. Future study was also proposed.